Dendrobium candidum aqueous extract attenuates isoproterenol-induced cardiac hypertrophy through the ERK signalling pathway - Yuan-Yuan Cao; Ke Li; Ying Li; Xiao-Ting Tian; Hui-Xue Ba; Aiping Wang; Xiao-Hui Li (Taylor & Francis Group, 2020)
Context The pharmacological functions of Dendrobium candidum Wall. ex Lindl. (Orchidaceae) in cardiac hypertrophy remains unclear. Objective To evaluate whether D. candidum aqueous extract (DCAE) can attenuate experimental cardiac hypertrophy. Materials and methods Cardiac hypertrophy in SD rats was induced by subcutaneously injection of isoproterenol (2 mg/kg), once a day for ten days. Rats were gavaged with DCAE (0.13 and 0.78 g/kg) daily for one month. At the end of treatment, measurement of left ventricular systolic pressure (LVSP), heart-to-body weight ratio (HW/BW), left ventricular/tibia length (LV/TL), atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP) levels, haematoxylin-eosin staining, and Masson's trichrome staining were conducted. In cultured H9c2 cells, DCAE (2 mg/mL) and U0126 (10 μM) were added 2 h before the isoproterenol (10 μM) stimulus. Phalloidin staining was used to evaluate cellular hypertrophy. The mRNA expression of ANP and BNP was measured by qRT-PCR. The expression of p-ERK was determined by immunoblotting. Results DCAE treatment significantly reduced the following indicators in vivo: (1) the LVSP (16%); (2) HW/BW (13%); (3) LV/TL (6%); (4) ANP (39%); (5) BNP (32%). In cultured H9c2 cells, phalloidin staining showed that DCAE relieved cellular hypertrophy (53% reduction). Furthermore, immunoblotting showed that DCAE can significantly inhibit p-ERK protein expression in vivo and in vitro (39% and 27% reduction, respectively). Discussion and conclusions DCAE prevents cardiac hypertrophy via ERK signalling pathway and has the potential for treatment of cardiac hypertrophy.